2020
DOI: 10.1101/2020.03.03.975193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extended amygdala-parabrachial circuits alter threat assessment to regulate feeding

Abstract: 29An animal's evolutionary success depends on the ability to seek and consume foods while 30 avoiding environmental threats. However, how evolutionarily conserved threat detection circuits 31 modulate feeding is unknown. In mammals, feeding and threat assessment are strongly 32 influenced by the parabrachial nucleus (PBN), a structure that responds to threats and inhibits 33 feeding. Here, we report that the PBN receives dense inputs from the bed nucleus of the stria 34 terminalis (BNST), an extended amygdala … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Although a functional division in the PBN is plausible, our results (particularly based on Pdyn expression) suggest that this conclusion warrants further study using high resolution approaches. It is also important to note that we recently observed that modulation of Pdyn PBN neurons can replicate behavioral effects that were once attributed solely to CGRP neurons in the PBN, and while these two populations are genetically distinct, similar behavioral effects were observed ( Bhatti et al, 2020 ). Interestingly, Yang et al observe hyperthermia in response activation of VGLUT2+ PBN neurons in some animals but with activation VGLUT2 PBN→POA projecting cells raising questions for future study about hypothermia activated PBN neurons and what their projection targets are.…”
Section: Discussionmentioning
confidence: 71%
“…Although a functional division in the PBN is plausible, our results (particularly based on Pdyn expression) suggest that this conclusion warrants further study using high resolution approaches. It is also important to note that we recently observed that modulation of Pdyn PBN neurons can replicate behavioral effects that were once attributed solely to CGRP neurons in the PBN, and while these two populations are genetically distinct, similar behavioral effects were observed ( Bhatti et al, 2020 ). Interestingly, Yang et al observe hyperthermia in response activation of VGLUT2+ PBN neurons in some animals but with activation VGLUT2 PBN→POA projecting cells raising questions for future study about hypothermia activated PBN neurons and what their projection targets are.…”
Section: Discussionmentioning
confidence: 71%
“…Another study that showed the opposing roles of these populations focused on their projections to the parabrachial nucleus (PB), a small pontine structure that has been implicated in a number of functions including feeding ( Kim et al, 2020 ; Palmiter, 2018 ). In this study, optogenetic stimulation of the axon terminals of BNST Vglut2 neurons in the PB suppressed feeding in food-deprived mice, induced place avoidance, supported negative reinforcement of an operant behavior to turn off the stimulation, and increased anxiety-like behavior ( Bhatti et al, 2020 ). In contrast, stimulating the terminals of BNST Vgat neurons increased food intake in ad libitum fed mice, induced place preference, supported positive reinforcement of an operant task to turn on the stimulation, had an anxiolytic effect, and suppressed freezing responses to a learned auditory threat signal.…”
Section: Opposite Regulation Of the Diverse Behavioral Statesmentioning
confidence: 68%
“…Notably, while the activation of both the BNST Vgat -PB and vBNST Vgat -VTA projections supported place preference and reduced anxiety-like behaviors, only the activation of the former increased feeding behavior ( Bhatti et al, 2020 ; Jennings et al, 2013a ). Furthermore, a separate study showed that optogenetic stimulation of the projection from the anterior dorsal part of the BNST (adBNST, mostly composed of GABAergic neurons) to the VTA supports place preference, but does not affect anxiety-like behavior ( Kim et al, 2013 ).…”
Section: Anatomical and Functional Heterogeneitymentioning
confidence: 98%
See 2 more Smart Citations